2020
DOI: 10.1007/s13555-020-00394-8
|View full text |Cite
|
Sign up to set email alerts
|

Novel Coronavirus Disease (COVID-19) and Biologic Therapy for Psoriasis: Successful Recovery in Two Patients After Infection with Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2)

Abstract: The outbreak of the novel coronavirus known as SARS-CoV-2 (severe acute respiratory syndrome coronavirus 2) causing COVID-19 was first reported in late December 2019. Many patients with psoriasis on biologic therapy have asked their medical providers about the effect of biologics on COVID-19. However, it is currently unknown how biologic therapy for psoriasis might impact patients with psoriasis and COVID-19. In this article, we report on the clinical course of two patients on biologic medication for psoriasis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 7 publications
0
18
0
Order By: Relevance
“…Also, case series (10,11) indicated that the biologic seemed to be protective against the onset and the severity of COVID-19. Further, 3 case reports (12)(13)(14) demonstrated the mild form of COVID-19 in psoriatic patients. However, the strengths (novelty, high applicability in the pandemic of COVID-19, and in depth analysis) and limitations of such studies (the absence of generalization, lack of cause-effect relationship, and publication bias) should be considered while their results are interpreted.…”
Section: Discussionmentioning
confidence: 99%
“…Also, case series (10,11) indicated that the biologic seemed to be protective against the onset and the severity of COVID-19. Further, 3 case reports (12)(13)(14) demonstrated the mild form of COVID-19 in psoriatic patients. However, the strengths (novelty, high applicability in the pandemic of COVID-19, and in depth analysis) and limitations of such studies (the absence of generalization, lack of cause-effect relationship, and publication bias) should be considered while their results are interpreted.…”
Section: Discussionmentioning
confidence: 99%
“…Withholding biologics and transitioning to safer alternatives may be considered to avoid complications, and initiation of biologic therapy is not recommended in active SARS-CoV-2 infection [ 195 198 ]. Moreover, patients should be carefully assessed before a biologic is discontinued because of the risk of diminished treatment response with re-initiation and the development of antibodies, erythroderma, or disease flare [ 196 , 199 ]. Our treatment algorithm focuses on patients who are negative for COVID-19 and are not at high-risk for SARS-CoV-2 infection.…”
Section: Comorbid Conditions and Special Populationsmentioning
confidence: 99%
“…Two cases have been reported of patients with psoriasis receiving biologics who achieved full recovery from COVID-19 with outpatient supportive therapy [ 199 ]. One patient started ustekinumab 3 years prior to COVID-19 diagnosis.…”
Section: Comorbid Conditions and Special Populationsmentioning
confidence: 99%
“…Biologics for the treatment of psoriasis inhibit TNF, IL-12/23, IL-23, and IL-17 ( Table 2 ). There are many case reports of psoriasis patients who presented with mild COVID-19 infections during biologic therapy and had favorable outcomes [ 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ]; however, biologic therapy did not suppress the progression of COVID-19, which resulted in acute respiratory distress syndrome (ARDS) [ 39 ]. In COVID-19 patients, higher levels of TNF have been observed [ 40 ].…”
Section: Biologics For Psoriasismentioning
confidence: 99%